KERAGAMAN LUMUT KERAK SEBAGAI BIOINDIKATOR KUALITAS HUTAN DI KAWASAN CEMORO SEWU MAGETAN JAWA TIMUR - Efri Roziaty (Universitas Lambung Mangkurat, 2023)
This study determined the diversity of lichens as a bioindicator of forest quality in the Cemoro Sewu area, Magetan, East Java. A descriptive qualitative research with exploratory research using a plotless sampling technique was used in the hiking trail areas. The results contained 13 species of lichen, namely Anaptychia palmulata, Cryptothecia striata, Dirinaria picta, Graphis scripta, Haematomma puniceum, Lecanorasp, Lepraria lobbyficans, Lobaria pulmonaria, Parmelia saxatilis, Parmelia sulcate, Pertusaria amara, Pseudevernia furfuracea, and Usnea sp. The diversity index (H') of was classified as moderate, which of 2.44. The quality of the Cemoro Sewu forest based on the value of lichen diversity and identification of its abiotic conditions was categorized as a good and healthy forest.